Methods of journalistic writing in Iraq after 4/9/2003 An analytical study of the scale of the prevailing journalistic arts and its relationship to the nature of The version after the US occupation of Iraq in 2003 (Journal of the College of Basic Education, 2023)
Today, the Iraqi press stands at a crossroads, as it is facing the third occupation.of Iraq in its history which is supposed to have begun in 1869.The nice irony here is that it appeared on this date with the Ottoman occupation.If the press of an occupying power has started, it represents the viewpoints of the occupiers and publishes their messages.and their data.Despite the fact that the Iraqi press is going through a difficult (pabour) today, as it is facingA unique situation represented in the fall of a regime that believed in centralization, totalitarianism, and one party.The red lines and the mixed rubber instructions on one side and on the other side are facingThe press is a military occupation proven in accordance with Security Council resolutions, and from a third side it is facingSerious attempts were made to rebuild the joints of the state that completely collapsed on 4/9/2003.She is trying to find her professional formations, honor codes, and instructions for rebuilding the house.Journalist according to a new view of the role of the press in Iraq, which is not an easy task.And because journalism as a profession does not end with the end of regimes, even if it was employed throughThe authorities sometimes, according to the political system’s vision of the mission and roles of the press, and the nature ofHis dealings with public freedoms, including freedom of the press, ended on the morning of 4/9/2003.